Answer:
[tex]R= 2.6[/tex]
Step-by-step explanation:
Given
[tex]f(x) = 40e^{.06t[/tex]
[tex][a,b] = [0,3][/tex]
Required
Determine the average rate of change (R)
This is calculated as follows:
[tex]R = \frac{f(b) - f(a)}{b - a}[/tex]
Where
[tex]a = 0[/tex] and [tex]b = 3[/tex]
Substitute 0 for a and 3 for b
[tex]R = \frac{f(3) - f(0)}{3 - 0}[/tex]
[tex]R = \frac{f(3) - f(0)}{3}[/tex]
[tex]R = \frac{1}{3}[f(3) - f(0)][/tex]
Calculate f(3)
[tex]f(x) = 40e^{.06t[/tex]
[tex]f(3) = 40e^{.06*3}[/tex]
[tex]f(3) = 40e^{0.18}[/tex]
[tex]f(3) = 40 * 1.197[/tex]
[tex]f(3) = 47.88[/tex]
Calculate f(0)
[tex]f(x) = 40e^{.06t[/tex]
[tex]f(0) = 40e^{.06*0}[/tex]
[tex]f(0) = 40e^{0}[/tex]
[tex]f(0) = 40*1[/tex]
[tex]f(0) = 40[/tex]
So, the expression:
[tex]R = \frac{1}{3}[f(3) - f(0)][/tex]
[tex]R= \frac{1}{3}[47.88 - 40][/tex]
[tex]R= \frac{1}{3}[7.88][/tex]
[tex]R= 2.62666666667[/tex]
[tex]R= 2.6[/tex]
Hence, the average rate of change is approximately 2.6